PREVALENCE AND DISTRIBUTION OF ORAL MUCOSAL DISORDERS AND DENTAL CARIES: A REVIEW OF THE LITERATURE - Ismoilov Ibodjon Imomjonovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Summary. Dental caries is a common disease among the population of different geographical zones and countries of the world. explains the complexity of the pathological condition. Taking into account the peculiarities of the occurrence and development of caries in children, it is important to study and implement in the treatment and prevention of dental caries in children both remineralizing and microbiological colonizing effects in the oral cavity. this is a task.